The molecular characteristics of extended-spectrum β-lactamases (ESBL), Carbapenem-Resistant Enterobacterales (CRE) and susceptible isolates of Klebsiella pneumoniae and Escherichia coli in Hospital Pakar Universiti Sains Malaysia (HPUSM), Kelantan, Malaysia - Nur Husna Shahimi,; Zeti Norfidiyati Salmuna,; Mawaddah Mohd Azlan,; Haslizai Hassan,; Nik Yusnoraini Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Multidrug-resistance Klebsiella pneumoniae (MDR-KP) has become a major challenge to clinicians as it caused significant morbidity and mortality among hospitalized patients. This study aims to determine the antibiotic susceptibility profiles of 17 K. pneumoniae strains isolated to different antimicrobial agents and to characterize the genes encoding extended-spectrum β-lactamase (ESBL), AmpC and (Carbapenem Resistance Enterobacteriacae (CRE) phenotypes by using VITEK AST (Antimicrobial Susceptibility Test), phenotypic disk confirmatory test (PDCT) and polymerase chain reaction (PCR). Out of 17 K. pneumoniae isolates tested, seven (41.2%) were confirmed to be ESBL producers, carrying blaTEM (1; 14.3%), blaSHV (1; 14.3%), blaCTXM-1 (4; 57.14%), blaCTXM-14 (2; 28.6%) and co-existence of both blaTEM and blaCTXM-1 (1; 14.3%) genes, while four K. pneumoniae (23.5%) isolates were CRE strains, carrying co-existence of blaTEM and blaCTXM-1 genes, as well as blaNDM-1 (4; 100%). blaTEM and blaCTXM genes were the most predominant genes detected in both K. pneumoniae ESBL and CRE isolates and blaNDM-1 genes was detected in K. pneumoniae CRE isolates which were in line with other findings worldwide. Understanding this link highlights the need for strategic antibiotic usage in healthcare settings by providing a deeper understanding of antibiotic resistance trends in multidrug resistant (MDR) organisms.